TOURISM ACTIVITIES AND TOURISM MANAGEMENT PRACTICES AMONG SELECTED TOURIST ATTRACTIONS IN GUIUAN, EASTERN SAMAR - Mary Dhangineth M. Padrilan; Rizza Joy M. Bergado; Erika Odron; Jeane E. Omlang; Zosimo E. Cabides Jr. (Western European Studies, 2023)
The role of tourism management is to develop effective strategic plan in order to guarantee a possible growth of a destination, without having a negative impact on the resources, either natural or civilian of the destination itself. Tourist spots follow a life-cycle (evolution cycle) based on a price factor (a greater attractiveness of an area means a greater willingness to pay of the tourists) and a trend factor (related to the fame of the area and to the evolution of tourists’ tastes and habits). These factors mark the tourism in the contents and in the methods of production and consumption, related to the concepts of supply and demand, two dimensions that must be always connected with the principles of growth, accessibility and sustainability. (Andreis and Carioni, 2019).
Keywords: connected; principles; sustainability